Exploring the Multi–Target Neuroprotective Chemical Space of Benzofuran Scaffolds: A New Strategy in Drug Development for Alzheimer’s Disease - Cabrera-Pardo, Jaime R.; Fuentealba, Jorge; Gavilán, Javiera; Cajas, Daniel; Becerra, José; Napiórkowska, Mariola (Frontiers in Pharmacology, 2020)
Alzheimer’s disease (AD) is an irreversible and progressive neurodegenerative disorder that slowly destroys memory. The precise mechanism of AD is still not entirely understood and remains under discussion; it is believed to be a multifactorial disease in which a number of mechanisms are involved in its pathogenesis. Worldwide, near 37 million people suffer from the effects of AD. As a cause of death for elderly, it is predicted that AD will rank third in the coming years, just behind cancer and heart disease. Unfortunately, AD remains an incurable condition. Despite the devastating problems associated with AD, there are only four FDA approved drugs for palliative treatment of this pathology. Hence, renewed scientific efforts are required not only to uncover more insights into the AD process but also to develop more efficient pharmacological tools against this disease. Due to the complexity and multiple mechanisms at play in the progression of AD, the development of drugs by rational design is extremely difficult. The existing drugs to fight against Alzheimer’s have had limited success, mainly due to their ability to modulate only one of the mechanisms involved in AD. As opposed to single-targeted strategies, the identification of small molecules able to affect multiple pathways involved in Alzheimer’s is a promising strategy to develop more efficient medicines against this disease. Central to existing efforts to develop pharmaceuticals controlling AD is the discovery of new chemicals displaying strong neuroactivity. Benzofurans are privileged oxygen containing heterocycles that have a strong neuroprotective behavior, inhibiting several of the important events involved in the AD process. In this review an approach is presented that relies on expanding the neuroprotective chemical space of benzofuran scaffolds by accessing them from Andean–Patagonian fungi and synthetic sources (chemical libraries). The exploration of the neuroprotective chemical space of these scaffolds has the potential to allow the discovery of substitution patterns that display multi-target neuroactivity against multiple events involved in AD. This benzofuran chemical framework will establish a multi-target chemical space that could set the basis for the development of super drugs against AD.